Edukacja/Migracja, czyli zamierzony rym - Wójcik-Dudek, Małgorzata (Postscriptum Polonistyczne, 2020)
The article aims at presenting a critical review of the book Edukacja. Migracja. Edukacja międzykulturowa w kontekście kryzysu migracyjnego z perspektywy krajów V4 [Education. Migration. Intercultural education in a context of migration crisis regarded from V4 countries perspective] edited by Emilia Kledzik and Małgorzata Parczyk and devoted to the issue of intercultural education. The review author tries to define the source of such reflection. She argues that John Dewey’s concept of education presented in his work Democracy and Education is essential for creating a contemporary model of intercultural education. The concept of the American pedagogue remains valid because it is based on viewing education as being a result of combining heritage with personal experience. It emphasises respect for otherness and the belief in universalizing different experiences, which must lead to communication. In the article author’s opinion, the reviewed book consists of texts constituting a contemporary commentary to John Dewey’s ideas.